Florence Gaignerot-Driessen and Jan Driessen. Cretan Cities: Formation and Transformation - Iacovou, Maria (Journal of Greek Archaeology, 2017)
How often does one read a review volume from cover to cover? Cretan cities was one of those rare experiences. It felt almost like reading a well-written novel where one’s interest is escalating from chapter to chapter, only in this case there were not one but altogether ten authors: six chapters were written by a single author (E. Tegou; D. Lefèvre-Novaro; A. Pautasso; S. Wallace; D. Haggis; J. Whitley) and two by a pair of authors (V. Zographaki and A. Farnoux; D. Viviers and A. Tsingarida).